(untitled) (Brazilian Journal of Behavioral and Cognitive Therapy, 2011)
The behavior-analytic therapy of choking phobia in a 35 yrs-old woman, a case previously published focusing strictly on its psychiatric aspects, is now presented concerning specific life history determinants of both choking phobia and other responses of the same functional class, all of them involving experiential avoidance. Psychoeducation included detailed functional analysis of choking phobia and relationship problems, correlating both set of phenomena under a single perspective. By means of therapist-assisted graded exposure sessions to different sets of foods, according to a multiple baseline design, the fear subsided and ingesta returned to normal levels. In parallel, significant changes occurred in relationship patterns. Relational frame theory provides a possible explanation to the fact that the client promoted extensive and progressive changes in her eating pattern and relationship with significant others.